Meta-Analysis: Malaria Vaccine Effectiveness - Pardomuan Robinson Sihombing (MEJORA Medical Journal Awatara, 2026)
Background: Malaria remains a significant global public health problem with a disproportionate impact on children in endemic areas. With the approval of the RTS,S/AS01 and R21/Matrix-M by WHO, a comprehensive evaluation of the effectiveness of malaria vaccines is crucial to inform public health policy. Aims: This study aimed to evaluate the effectiveness of malaria vaccines through a systematic review and meta-analysis of intervention studies that compared treatment versus control groups. Methods: The research methodology followed the PRISMA guidelines with systematic searches in PubMed and Scopus databases for open-access primary articles reporting randomized controlled clinical trials of malaria vaccines. Inclusion criteria included intervention studies (vaccine vs. placebo/control), child populations, and malaria clinical outcomes. Meta-analysis was performed using the Jamovi package ESCI with a random effects model to calculate the pooled risk ratio and 95% confidence interval, and prediction interval. Results: The results of the meta-analysis showed that the RTS,S/AS01 provided a 36.3% efficacy against clinical malaria at follow-up, while the R21/Matrix-M vaccine showed a higher efficacy of 70.0%, especially in the seasonal transmission setting. Forest plots indicated significant heterogeneity between studies (I²>98%, p <0.001) and a wide prediction interval, reflecting the expected variability across different epidemiological settings. Conclusion: The study's conclusions suggest the malaria vaccine, particularly R21/Matrix-M, provide substantial protection against clinical malaria with an acceptable safety profile, but require a booster dose strategy to maintain long-term efficacy. The implications of these findings support the implementation of malaria vaccination programs as a complement to vector control interventions in efforts to eliminate global malaria.